2016
DOI: 10.1111/jdv.13859
|View full text |Cite
|
Sign up to set email alerts
|

Calcipotriol plus betamethasone dipropionate aerosol foam provides superior efficacy vs. gel in patients with psoriasis vulgaris: randomized, controlled PSO‐ABLE study

Abstract: BackgroundFixed combination calcipotriol 50 μg/g (Cal) plus betamethasone 0.5 mg/g (BD) foam has been developed as a new treatment option for patients with psoriasis.MethodsThe randomized, parallel‐group, investigator‐blinded Phase III, 12‐week PSO‐ABLE study compared the efficacy and safety of Cal/BD foam with Cal/BD gel. Patients aged ≥18 years with mild‐to‐severe psoriasis were randomized 4:4:1:1 to once‐daily Cal/BD foam, Cal/BD gel, foam vehicle or gel vehicle (NCT02132936). The primary efficacy endpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(177 citation statements)
references
References 28 publications
5
168
1
3
Order By: Relevance
“…The efficacy and safety of fixed combination calcipotriol 50 μg/g (Cal) and betamethasone 0.5 mg/g as dipropionate (BD) have been confirmed in a number of studies 14, 15, 16, 17, 18, 19, 20, 21. The ointment and gel formulations of this fixed combination are established first‐line treatments for psoriasis 22.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The efficacy and safety of fixed combination calcipotriol 50 μg/g (Cal) and betamethasone 0.5 mg/g as dipropionate (BD) have been confirmed in a number of studies 14, 15, 16, 17, 18, 19, 20, 21. The ointment and gel formulations of this fixed combination are established first‐line treatments for psoriasis 22.…”
Section: Introductionmentioning
confidence: 96%
“…The ointment and gel formulations of this fixed combination are established first‐line treatments for psoriasis 22. An aerosol foam formulation, which was developed to enhance adherence and increase the therapeutic options available to patients, has been shown to be effective and well tolerated 17, 23. The Phase IIIb PSO‐INSIGHTFUL study was designed to assess the patient‐reported factors that influence preference following once‐daily topical treatment with Cal/BD foam and gel, whilst minimizing the impact of efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated the superior efficacy of Cal/BD aerosol foam compared with traditional formulations such as ointments, gels, and lotions (Table 2) 15,[22][23][24] The increased efficacy of Cal/BD aerosol foam is also associated with a similar safety profile, as demonstrated in a pooled safety analysis comparing fixed-dose combination Cal/BD aerosol foam with BD foam, Cal foam, Cal/BD ointment, and vehicles (foam and ointment) 25 …”
Section: An Innovative Drug Delivery Formulation Results In Improved mentioning
confidence: 99%
“…[2][3][4][5]  We assessed the clinical characteristics, treatment patterns, and other physician and patient characteristics, adverse events, and resource utilizations in patients using Cal/BD foam to treat plaque psoriasis.…”
Section: Disclosuresmentioning
confidence: 99%